Experimental Investigation On The Load Carrying Capacity Of Modified Purlin To Rafter Connection - Humayunkabir, Sheikh Hazwan (Universiti Sains Malaysia, 2017)
In Malaysia, almost all houses in rural area are non-engineered structures. The roof of these houses is susceptible to failure and many types if roofing failure can be expected. This study examines the pull-out capacity of several simple connections meant for tying the timber purlin to rafter. The types of connections are single nail, double nail, nail plus metal strap and nail plus rope. The tests were conducted on timber type Damar Minyak and Dark Red Meranti, both are classified under strength group 5 and 6. The wind load was applied in the form of pull-out force generated via in-house frame and Universal Testing Machine. The results showed that, for single nail connection, two phases of response were observed. Other types of connections showed three distinct phases from beginning until failure. This phenomenon is particularly true for both types of timber. In the case of timber type Damar Minyak, the maximum pull-out capacity exhibited by the nail and metal strap connection (1.55 kN) followed by nail and rope (1.485 kN), double nail (0.825 kN) and single nail (0.445 kN). However, for timber type Dark Red Meranti, the use of double nail spaced at 30 mm apart exhibited the highest pull-out capacity (2.5 kN) followed by nail and metal strap (1.8 kN), nail and rope (1.53 kN) and single nail (1.22 kN). It was also noted that stronger timber grade developed higher nail to timber connection compared to lower timber grade. The most efficient connection for timber type Damar Minyak and Dark Red Meranti was found to be nail plus rope and double nail, respectively.